Effects of applying blended learning based on the ADDIE model in nursing staff training on improving theoretical and practical operational aspects - Luo, Runfen; Li, Jing; Zhang, Xiaoni; Tian, Dan; Zhang, Yi (Frontiers in Medicine, 2024)
Objective To assess the impact of blended learning, based on the ADDIE model, on theoretical and practical aspects of nursing staff training. Methods Retrospective analysis of data from 87 nursing staff members in Xi’an Qinhuang Hospital divided into control (n = 43) and observation (n = 44) groups. The control group received conventional training, while the observation group underwent blended learning. Comparative analysis included theoretical knowledge, practical skills, self-directed learning, critical thinking, and teaching satisfaction. Results The observation group showed significantly higher theoretical knowledge, practical skills, self-directed learning, critical thinking, and teaching satisfaction compared to the control group (p < 0.05). Conclusion Blended learning based on the ADDIE model enhances nursing staff training outcomes, improving theoretical knowledge, practical skills, self-directed learning, critical thinking, and teaching satisfaction. This approach presents a promising method for enhancing nursing education and warrants further implementation in clinical settings.